NGF and proNGF Reciprocal Interference in Immunoassays: Open Questions, Criticalities, and Ways Forward - Malerba, Francesca; Paoletti, Francesca; Cattaneo, Antonino (Frontiers in Molecular Neuroscience, 2016)
The homeostasis between mature neurotrophin NGF and its precursor proNGF is thought to be crucial in physiology and in pathological states. Therefore, the measurement of the relative amounts of NGF and proNGF could serve as a footprint for the identification of disease states, for diagnostic purposes. Since NGF is part of proNGF, their selective identification with anti-NGF antibodies is not straightforward. Currently, many immunoassays for NGF measurement are available, while the proNGF assays are few and not validated by published information. The question arises, as to whether the commercially available assays are able to distinguish between the two forms. Also, since in biological samples the two forms coexist, are the measurements of one species affected by the presence of the other? We describe experiments addressing these questions. For the first time, NGF and proNGF were measured together and tested in different immunoassays. Unexpectedly, NGF and proNGF were found to reciprocally interfere with the experimental outcome. The interference also calls into question the widely used NGF ELISA methods, applied to biological samples where NGF and proNGF coexist. Therefore, an immunoassay, able to distinguish between the two forms is needed. We propose possible ways forward, towards the development of a selective assay. In particular, the use of the well validated anti-NGF αD11 antibody in an alphaLISA assay with optimized incubation times would be a solution to avoid the interference in the measurement of a mixed sample containing NGF and proNGF. Furthermore, we explored the possibility of measuring proNGF in a biological sample. But the available commercial kit for the detection of proNGF does not allow the measurement of proNGF in mouse brain tissues. Therefore, we validated an SPR approach for the measurement of proNGF in a biological sample. Our experiments help in understanding the technical limits in the measurement of the NGF/proNGF ratio in biological samples, and propose concrete solutions towards the solution of this problem.